THE SPECIFICS OF THE MARKETING ACTIVITY OF INDIVIDUAL SUBJECTS OF THE AGRARIAN MARKET IN CONDITIONS OF COMPETITION - BURDYAK, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Today, agrarian marketing is a rapidly developing field. Marketing tools are actively used in managing production and sales processes of agricultural production enterprises. However, the theory of agrarian marketing itself is still in its formative stage and contains numerous unresolved issues. Addressing these questions is essential for creating a comprehensive understanding of agrarian marketing and for enabling its most effective application. Questions arise even at the initial stage of understanding the essence and content of agrimarketing, specifically in its conceptual framework. The purpose of this article is to examine the specifics of marketing activities of individual agrarian market actors under competitive conditions, as well as to determine the role of the agricultural machinery production and material-technical supply sectors within the agrarian marketing system. Additionally, it seeks to justify the necessity of recognizing this sector as an important component of agrarian marketing. The subject of this research is the conceptual framework of agrarian marketing and the specifics of marketing activities of individual agrarian market actors under competition. Research Methods: The study utilizes comparative analysis, detailing and generalization, comparison methods, systematization, analysis, and synthesis. The main hypothesis of the research assumes that recognizing the agricultural machinery production sector as a component of agrarian marketing, along with agricultural machinery and equipment manufacturers as subjects of agrarian marketing, will lead to qualitative changes in the development of marketing programs for agricultural producers. Presentation of the Main Material. The theory of agrarian marketing continues to evolve, and one of the critical questions concerning its conceptual framework is identifying the components and subjects of agrarian marketing. It has been established that the basic approach considers the agricultural production and processing sectors as primary components. The material-technical supply sector, traditionally including the provision of mineral fertilizers, crop protection products, veterinary services, transport and warehousing, material-technical support, and other infrastructural components, is also recognized as a component. The question remains open regarding agricultural machinery manufacturing enterprises: are they subjects of agrarian marketing, and can they be regarded as components of this type of marketing? This theoretical question has practical significance. The clear understanding of roles in the agrarian market and the impact of infrastructure enterprises on the overall outcome is crucial for the formation of marketing programs for agricultural producers, especially under competitive conditions, where it is vitally important. In various respects, the marketing activities of agricultural machinery manufacturers can be characterized as following an industrial marketing concept. However, the author believes that it is crucial to analyze the level of influence of specific agrarian marketing features on the activities of agricultural machinery manufacturers in this context. It has been identified that these enterprises are subject to the same factors and conditions that affect agricultural producers and must consider them in their operations. Consequently, all marketing decisions of agricultural machinery manufacturers align with the marketing activities of agrarians. Moreover, the future development of agricultural machinery manufacturing entirely depends on the marketing and managerial decisions of agriproducers as the primary customers. It is essential to understand that agricultural machinery manufacturers actively impact the agrarian market and agricultural production. By offering new machines and equipment, they encourage agrarians to adopt innovations, implement new work methods, and introduce new crops. In turn, agrarians stimulate the development of new machines and equipment with their demands and establish standards and requirements for quality, productivity, and reliability. This collaboration is complementary and mutually beneficial, making it the most effective approach. Therefore, the theoretical resolution to recognize agricultural machinery, spare parts, and consumables manufacturers as active and essential subjects of agrarian marketing should transition into a practical dimension: agrarians and processing enterprises should include agricultural machinery manufacturers and agricultural supply enterprises in their marketing monitoring system. They should actively follow the latest developments in the agricultural machinery and equipment market and influence this market by creating demands for new machinery and technologies.